Effect of Polypropylene Fiber on Geopolymer Concrete Blended with Three Different Mineral Admixtures - C. Manoj Kumaar, B. Priyadharshini, Jeyaveerapandian G, Shobha Rani Arangi, Inthirajith. M (International Journal of Advanced Science and Technology, 2020)
Cement concrete is the material mostly used for building purposes, often consisting of ordinary Portland cement. An alternative such as Geopolymer concrete (GPC) has become more important, due to the environmental concerns of cement production.  Geopolymer concrete consists of mineral admixtures such as Fly ash, Ground Granulated Blast Furnace Slag (GGBS), Rice Husk Ash (RHA) which are known as waste materials. Because of its ample amount of availability, mineral admixtures can be used as an alternative for ordinary Portland cement. In this study, Geopolymer concrete contains Fly ash, Ground Granulated Blast Furnace Slag, Rice Husk Ash, Coarse and Fine aggregates. Alkali activation of mineral admixtures is done by sodium hydroxide (SH) and sodium silicate (SC) which is called Alkali Activator Solution (AAS). Polypropylene (PP) fibers are used in varying percentages to improve the mechanical properties of geopolymer concrete. Fiber adopted in this study are 0%, 0.5%, 1%, 1.5%, 2%, 2.5% and 3%. Properties like Compressive strength, Split tensile strength, and Flexural strength of geopolymer concrete are carried out on the 7th and 28th day. For the optimum percentage of polypropylene fiber geopolymer mix, nominal geopolymer concrete mix, and conventional cement-based concrete mix are examined for load-deflection behaviour. A cost comparison is done with Conventional cement-based concrete. Based on the test results, 2% of Polypropylene Fiber is optimum for geopolymer concrete in this study. Keywords: Fly ash, GGBS, RHA, Ambient Curing, Polypropylene Fiber and Geopolymer.